Pemberdayaan Komunitas Sekolah: Prioritas Masalah dan Peningkatan Pemahaman PHBS di SDN 16 Benteng Jaya - Hasibuan, Rapotan; Pasaribu, Anissya Fahira; Ayuandini, Friska; Al-Kahfi, Moh. Keanu; Fakhriansyah, Luthfi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Clean and Healthy Living Behavior (PHBS) among school-aged children in Indonesia faces significant challenges, as found: the low awareness of PHBS at SDN 16 Benteng Jaya, Batu Bara Regency. The objective of this activity is to identify, and formulate efforts to address school environmental health issues to enhance students' knowledge about personal and environmental hygiene. The method includes coordination with the school authorities, socialization of PHBS to 32 students in grades 4 and 5, assistance in problem identification through a Panel Discussion with the principal and teachers, and evaluation of students' knowledge using pre-test and post-test. The results of problem priority identification using the Bryant method show